Impact of Design of Experiments in the Optimisation of Catalytic Reactions in Academia - Nori, Valeria; Sinibaldi, Arianna; Pesciaioli, Fabio; Carlone, Armando (Synthesis, 2022)
Design of Experiments (DoE) is extensively and routinely used in industry; however, in recent decades, it has gained increasing interest from academia in organic synthesis. The use of chemometrics is an attractive strategy to find the real optimum in chemical reactions, especially when affected by several variables. DoE has been applied in a growing number of synthetic transformations over the years, where it undoubtedly helps in the process of optimisation, saving costs and time. This review concisely discusses the chemometric basis of Design of Experiments and highlights several examples in which DoE is applied in organic synthesis.1 Introduction2 Chemometric Basis of DoE3 DoE Applied in Catalysis: Selected Examples3.1 DoE in Metal Catalysis3.2 DoE in Biocatalysis3.3 DoE in Organocatalysis4 Conclusions
Keywords: DoE; design; chemometrics; optimisation; screening; organic synthesis; catalysis